An Approach to Calculate Inverse of LR-Trapezoidal Fuzzy Matrix. Issue 1 (1st January 2022) - Zhuo, Quanxiu; Guo, Xiaobin
Abstract: In this paper, we devised a numerical algorithm for calculating the inverse of trapezoidal fuzzy numbers matrix. By analysing the existence of fuzzy inverse, the sufficient conditions are restricted. Furthermore, through calculating the approximate fuzzy inverse, the algorithm can be widely used in solving fully fuzzy linear system and it is validated by some given examples.